The use of drones for recreational impact monitoring of public lands - Sikorsky, Kristen D. (Kansas State University, 2020)
A significant increase in visitation to protected lands, such as wilderness areas, parks, and wildlife refuges, has been observed across the board, from the smallest of state parks to some of the largest national parks in the world. This rise in use has prompted concerns that visitation is degrading the plants, soils, water, and wildlife these areas were established to protect. The Interagency Visitor Use Management Framework (IVUMF) provides guidance to professionalize the process for the continued preservation of natural conditions and processes in protected natural areas and the sustained administration of high-quality recreational experiences. At the core of the IVUMF is the need to measure indicators and thresholds to both provide sound rationale on which to base new management decisions as well as measure the efficacy of enacted decisions over a long period of time. As public land managers seek to increase the implementation of simple and cost-effective methods to collect indicator and threshold data to address environmental and visitor experience concerns, drones may be the logical next step. This study analyzes the outcome of using a drone to formulate thresholds for two selected indicators, visitor-created trails and vegetation loss, in a newly established Kansas state park, Little Jerusalem Badlands. Up to a 42% loss in vegetation is already being observed in key areas of Little Jerusalem, as well as the formation of visitor created trails after the first three months of park opening consistent with the previously studied curvilinear rate of impact to a site. These results confirm the need for a simplified and reliable method to monitor a variety of environmental indicators in protected areas over the long-term to aid land management agencies in decision-making to reduce recreational impacts.
Keywords: Drone; Public Land; Recreational Impact; Interagency Visitor Use Management Framework; Conservation; Vegetation Loss